Analysis and implementation of a modular isolated zero‐voltage switching bidirectional dc–dc converter. Issue 8 (1st August 2014) - Sedaghati, Farzad; Hossein Hosseini, Seyed; Sabahi, Mehran; Gharehpetian, G.B.
Abstract : A new topology of modular isolated bidirectional dc–dc converter is proposed. The proposed modular converter has interesting features in terms of low switching losses, bidirectional power flow and less number of switching device. In comparison with similar topologies, the reduction in the switching device number does not decrease the proposed converter power rating. Also, the simple modular structure, high‐frequency operation, zero‐voltage switching (ZVS) capability and less number of switching device make the extended configuration of the proposed converter suitable for high‐power applications. The ZVS capability without using any auxiliary circuit is one of the most important specifications of the proposed converter. The design of the proposed converter, based on the connection of basic modules, is described and the steady‐state operation analysis is presented. The ZVS of the proposed converter both in turn‐on and turn‐off instants are studied and their criteria are derived in detail. The simulation and measurement results are presented to verify the effectiveness of the proposed converter.